Evaluation of a commercial ELISA for measurement of feline urinary alpha1-microglobulin (International Journal of Health, Animal Science and Food Safety, 2016)
Urinary alpha1-microglobulin (a1M) in people is a biomarker of renal tubular damage (Bazzi, 2001), butit has not yet been used in cats with chronic kidney disease (CKD).The aim of this study was to validate an ELISA test marketed for the measurement of feline a1M.Thirty-four urine supernatants collected from cats affected by or at risk for CKD were assayed by SDSAGE,to classify patients according to presence or absence of low molecular weight proteinuriasuggestive of tubular damage.Two samples with and one without tubular bands were used to evaluate intra-assay variability, linearityunder dilution (LUD) and spiking recovery test (SRT) of the ELISA. Then, a1M concentration wasmeasured in samples with (n°=10) or without (n°=25) tubular bands. The standard solution included inthe kit was also assayed by SDS-AGE.The intra-assay CVs was >20%. LUD and SRT showed that the test is not accurate. No significantdifference was found between a1M concentration in samples with and without tubular bands (medianvalues: 35.19 and 40.83 μg/mL respectively). SDS-AGE on the standard solution failed to identify bandswith molecular weight consistent with a1M but showed the presence of albumin.Results of this investigation did not support the use of this test to measure a1M in cats likely due to theabsence of a1M in the standard solution provided with the kit.
Keywords: Alpha1-microglobulin; urine; cat; validation; enzyme-linked immunosorbent assay; chronic kidney disease